Respiratory Syncytial Virus Aggravates Renal Injury through Cytokines and Direct Renal Injury - Zhai, Songhui; Hu, Lijuan; Zhong, Lin; Guo, Yannan; Dong, Liqun; Jia, Ruizhen; Wang, Zheng (Frontiers in Cellular and Infection Microbiology, 2016)
The purpose of this study was to investigate the relationship between renal injury and reinfection that is caused by respiratory syncytial virus (RSV) and to analyze the mechanism of renal injury. Rats were repeatedly infected with RSV on days 4, 8, 14, and 28, then sacrificed and examined on day 56 after the primary infection. Renal injury was examined by transmission electron microscopy and histopathology. The F protein of RSV was detected in the renal tissue by indirect immunofluorescence. Proteinuria and urinary glycosaminoglycans (GAGs), serum levels of albumin, urea nitrogen, and creatinine, secretion of cytokines, T lymphocyte population and subsets, and dendritic cell (DC) activation state were examined. The results showed that renal injury was more serious in the reinfection group than in the primary infection group. At a higher infection dose, 6×106 PFU, the renal injury was more severe, accompanied by higher levels of proteinuria and urinary GAGs excretion, and lower levels of serum albumin. Podocyte foot effacement was more extensive, and hyperplasia of mesangial cells and proliferation of mesangial matrix were observed. The maturation state of DCs was specific, compared with the primary infection. There was also a decrease in the ratio of CD4+ to CD8+T lymphocytes, due to an increase in the percentage of CD8+T lymphocytes and a decrease in the percentage of CD4+T lymphocytes, and a dramatic increase in the levels of IL-6 and IL-17. In terms of the different reinfection times, the day 14 reinfection group yielded the most serious renal injury and the most significant change in immune function. RSV F protein was still expressed in the glomeruli 56 days after RSV infection. Altogether, these results reveal that RSV infection could aggravate renal injury, which might be due to direct renal injury caused by RSV and the inflammatory lesions caused by the anti-virus response induced by RSV.